การเปรียบเทียบคุณภาพของแบบสอบวินิจฉัยแบบสามระดับสำหรับมโนทัศน์ที่คลาดเคลื่อนทางคณิตศาสตร์ที่ใช้ระดับความมั่นใจที่แตกต่างกัน - มนัสสิริ อินทร์สวาท (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purposes of this study were 1) to develop three-tier diagnostic tests of mathematical misconception using different levels of confidence, and 2) to compare quality of the tests of mathematical misconception using different levels of confidence. The participants were 72 students of the 2015 academic year. The instruments used in the research were 1) three-tier diagnostic tests using two levels of confidence (sure and not sure) and three levels of confidence (sure, quite sure and not sure) and 2) the diagnostic test using Thinking Aloud method. The data were analyzed by using descriptive statistics, Cramer’s V coefficient, the Pearson product-moment correlation coefficient Cronbach s alpha coefficient for reliability and Fisher’s z coefficient. The research findings were as follows: 1) The results of the development of three-tier diagnostic test of mathematical misconception using different levels of confidence were as follows: 1.1) The development of three-tier diagnostic test using two levels of confidence has diagnosed 8 characteristics (correct response, misconception, lucky guess, and lack of knowledge were 1, 3, 1 and 3 characteristics respectively). The percentage of the students with correct response, misconception, lucky guess, and lack of knowledge were 55.56%, 27.78%, 0.00%, and 33.33% respectively; 1.2) The development of three-tier diagnostic test using three levels of confidence has diagnosed 12 characteristics (correct response, misconception, lucky guess, and lack of knowledge were 1, 3, 2 and 6 characteristics respectively). The percentage of the students with correct response, misconception, lucky guess, and lack of knowledge were 63.89% 13.89%, 2.78%, and 30.56% respectively. 2) The comparisons of quality of the tests were as follows: 2.1) The reliability of the former test (α = .956) and the latter test (α = .949) showed no significant differences at 0.5 level; 2.2) The criterion-related validity of the latter test compared with the diagnostic test using Thinking Aloud method (Cramer’s V value ranged from .555 to .854) was higher than the former test (Cramer’s V value ranged from .516 to .777); 2.3) The criterion-related validity of the correlation of relationship between content and reason answers and confidence answers of the former one (r = .717) and the latter test (r = .745) showed no significant differences at 0.5 level; 2.4) the average percentages of misconceptions of the former test compared with the diagnostic test using Thinking Aloud method test (66.67%) and the latter test (58.33%) showed no significant differences at 0.5 level; and 2.5) The reliability and validity of the former test and the latter test showed no differences.